ANALISA POLITIK DAN EKONOMI SERTIFIKASI HALAL OLEH BPJPH DALAM PERSPEKTIF MAQASHID ALSYARIA - Wafa, Zamroni; Tanuri, Tanuri (Moderation | Journal of Islamic Studies Review, 2022)
This study aims to find out how the political and economic impact of BPJPH halal certification in the maqasid al-syariah perspective. The type of research used in this research is qualitative with the case study method used to examine an object, with the researcher acting as the key instrument. Data were collected through triangulation (combined) techniques, then analyzed inductively/qualitatively. In this qualitative research, the researcher explores an event, program, process, or activity. While the data collection technique used is the method of documentation. The Documentation Method is a document tracking carried out to obtain data in the form of journals, books, and online media as supporting data that correlates with the research focus. Data analysis includes data condensation, data presentation, and conclusion drawing. Based on the research results, BPJPH halal certification in implementing halal certification has the task of establishing rules/regulations, receiving and verifying product submissions to be certified halal from business actors (product owners), and issuing halal certificates along with halal labels. Meanwhile, in implementing halal standardization, it still refers to SJH LPPOM MUI. Meanwhile, the cost of halal certification will be charged to the state for the MSE category. In addition, there are two payment account posts, namely at BPJPH and LPH (LPPOM). Viewed from a political economy approach, the presence of BPJPH brings ideological, power, and economic interests. Business actors consider BPJPH halal certification to be two-way, both the administrative process and the certification fee. In the perspective of maqasid al-syariah, halal certification by BPJPH brings benefits, namely maintaining essential needs for human life. These important needs are commonly called al-maqhasid al-khamsah, among others, maintaining religion, soul, mind, lineage and property.